2019
DOI: 10.1016/j.redox.2019.101254
|View full text |Cite
|
Sign up to set email alerts
|

PINK1-parkin pathway of mitophagy protects against contrast-induced acute kidney injury via decreasing mitochondrial ROS and NLRP3 inflammasome activation

Abstract: Contrast-induced acute kidney injury (CI-AKI) occurs in more than 30% of patients after intravenous iodinated contrast media and causes serious complications, including renal failure and mortality. Recent research has demonstrated that routine antioxidant and alkaline therapy failed to show benefits in CI-AKI patients with high risk for renal complications. Mitophagy is a mechanism of selective autophagy, which controls mitochondrial quality and mitochondrial reactive oxygen species (ROS) through degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
308
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(326 citation statements)
references
References 47 publications
13
308
4
1
Order By: Relevance
“…Many studies have reported that PINK1/Parkin signaling controls the selective degradation of dysfunctional mitochondria by mitophagy in acute kidney disease (Zhao et al, 2017;Tang et al, 2018;Lin et al, 2019). In healthy mitochondria, PINK1 is constitutively inserted into the mitochondria inner membrane and rapidly degraded by proteolysis to keep a low level of expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that PINK1/Parkin signaling controls the selective degradation of dysfunctional mitochondria by mitophagy in acute kidney disease (Zhao et al, 2017;Tang et al, 2018;Lin et al, 2019). In healthy mitochondria, PINK1 is constitutively inserted into the mitochondria inner membrane and rapidly degraded by proteolysis to keep a low level of expression.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney disease, the PINK1/Parkin pathway was reported to play a dominant role in mitophagy (Lin et al, 2019). In this study, an activation of the PINK1/Parkin pathway at the time point of I6R12 was measured using immunofluorescence and immunoblot analysis.…”
Section: Pink1/parkin Pathway Was Activated By I/r In Hk-2 Cellsmentioning
confidence: 96%
“…Could enhancing mitophagy to clear these accumulated mitochondria effectively resist BMSCs stress-induced apoptosis and senescence? Mitophagy mediated by the PINK1-Parkin pathway is the most important way to clear damaged mitochondria 37,38 ; mitochondrial translocation of Parkin is very important to mitophagy 39 , and therefore increasing the content of Parkin in cells can be expected to increase mitochondrial translocation of Parkin and thus enhance mitophagy. Therefore, we used lentiviral vector-encoded Parkinenhanced green fluorescent protein (Lv-Parkin-EGFP) to transfect BMSCs.…”
Section: Enhancing Mitophagy Against Bmscs Stress-induced Apoptosis Amentioning
confidence: 99%
“…In recent years, vascular administration of iodinated contrast media (CM) has been widely used in patients undergoing diagnostic cardiac angiography and percutaneous coronary intervention [1]. Contrast-induced acute kidney injury (CI-AKI) occurs in more than 5-15% of patients after percutaneous coronary intervention via CM [2], which is associated with risk factors, such as advanced age, diabetes, and hypertension [3]. CI-AKI is the third most common cause of acute renal failure in hospitalized patients after hypoperfusion and nephrotoxic drugs [4].…”
Section: Introductionmentioning
confidence: 99%